Associations between pediatric asthma and adult non‐communicable diseases. Issue 2 (1st November 2020) - Juber, Nirmin F.; Lee, Chien‐Chang; Pan, Wen‐Chi; Liu, Jason J.
Abstract: Background: To date, there is no comprehensive study examining how asthma diagnosed in childhood or adolescence is associated with diagnoses of subsequent non‐communicable diseases (NCDs) during adulthood. Our study aimed to examine the associations between pediatric asthma and several adult NCDs, with temporality and long interval times between asthma and NCD diagnoses. Methods: We used RAND Indonesian Family Life Survey Fifth Wave (IFLS5) fielded in 2014‐2015, to study whether being diagnosed with pediatric asthma at 0‐19 years of age was associated with increased risks of hypertension, diabetes, rheumatoid arthritis, stomach diseases, kidney diseases, and heart diseases or stroke diagnosed in adulthood. We used the weighted Poisson regression adjusting for age, sex, urbanicity, and insurance status to estimate risk ratios. Subgroup analyses were performed by sex and age of asthma and other NCD diagnoses. Results: Pediatric asthma significantly increased risks of hypertension, diabetes, and stomach diseases diagnosed at 20 years of age or above. Males with pediatric asthma diagnosed at 0‐10 years of age had significantly higher risk of hypertension, while females with pediatric asthma diagnosed at 0‐10 years of age had significantly higher risks of diabetes and stomach diseases. Females with pediatric asthma diagnosed at 11‐19 years of age had significantly higher risks of diabetes, arthritis, stomach diseases, and kidney diseases. We also found varying associations by age of NCD diagnosis. Conclusion: Our results suggest pediatric asthma is associated with increased risks of several adult NCDs, and these associations may vary by sex and age of asthma and other NCD diagnoses.